Predictive validity of the N2 and P3 ERP components to executive functioning in children: a latent-variable analysis - Brydges, Christopher R.; Fox, Allison M.; Reid, Corinne L.; Anderson, Mike (Frontiers in Human Neuroscience, 2014)
Executive functions (EFs) are commonly theorised to be related yet separable constructs in adults, and specific EFs, such as prepotent response inhibition and working memory, are thought to have clear and distinct neural underpinnings. However, recent evidence suggests that EFs are unitary in children up to about 9 years of age. The aim of the current study was to test the hypothesis that peaks of the event-related potential (ERP) of specific EFs are related to behavioral performance, despite EFs being psychometrically indistinguishable in children. Specifically, N2 difference waveform (associated with cognitive control and response inhibition) and P3b peak (associated with updating of working memory) latent variables were created and entered into confirmatory factor analysis and structural equation models with a unitary executive functioning factor. Children aged 7-9 years (N = 215) completed eight measures of inhibition, working memory, and shifting. A modified flanker task was also completed during which EEG data were recorded. The N2 difference waveform and P3b mean amplitude factors both significantly correlated with (and were predictors of) the executive functioning factor, but the P3b latency factor did not. These results provide evidence of the electrophysiological indices of executive functions being observable before the associated behavioral constructs are distinguishable from each other. From this, it is possible that ERPs could be used as a sensitive measure of development in the context of evaluation for neuropsychological interventions.